Visualizing interfacial defect passivation in carbon‐based perovskite solar cells. (25th August 2022) - Kartikay, Purnendu; Sharma, Ashok Kumar; Behera, Siddharth; Bhargava, Parag; Yella, Aswani; Mallick, Sudhanshu
Summary: In perovskite solar cells (PSCs), defects and interfacial properties are critical and govern the device's performance. To enhance the performance, effective defect passivation and recombination reduction are crucial. This work reports phenethylammonium iodide (PEAI) treatment of lead‐excess perovskite film for low‐temperature carbon‐based PSCs. The PEAI post‐treatment leads to the formation of a crystallized (PEA)2 PbI4 2D layer on top of 3D perovskite. Apart from passivating the grain boundaries, the 3D/2D stack improves the interface between perovskite and carbon, reducing the interfacial recombination. Moreover, the passivation reduces the trap state density and provides improved energy alignment with the carbon layer. The reduced defects and non‐radiative recombination resulted in performance enhancement from 10.16% to 11.76% with good reproducibility. c‐AFM and photoluminescence (PL) imaging have been performed to visualize recombination sites and passivation quality post‐PEAI treatment. Furthermore, the voltage‐dependent PL imaging of PSCs reveals rapid quenching in the maximum power point regime substantiating efficient charge extraction in passivated devices. The prepared devices show noteworthy stability retaining around 60% of initial performance after 1000 hours. Abstract : PEAI post‐treatment of lead excess perovskite absorber layer forming 2D (PEA)2 PbI4 layer in low‐temperature carbon‐based perovskite solar cell. 3D‐2D stack effectively reduces trap states and non‐radiative recombination centers. Photoluminescence (PL) imaging to visualize recombination and its suppression post passivation. Voltage‐dependent PL imaging to study charge extraction at perovskite/carbon interface.